PENGARUH CITRA MEREK, KUALITAS PELAYANAN DAN SALURAN DISTRIBUSI PADA MINAT BELI KONSUMEN CV. AIR HIDUP DI LEGOK - BANTEN - Amalia, Rizki; Tajuddien, Rahadyan (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of brand image, service quality and distribution channels on purchasing interest in CV. Air Hidup. The method used is quantitative. The sampling technique used the ancient rao formula and a sample of 100 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that brand image has a significant effect on purchasing interest with a coefficient of determination value of 43% and the hypothesis test shows that t count > t table or (8.597 > 1.948). Service quality has a significant effect on purchase interest with a coefficient of determination value of 29.6% and hypothesis testing obtained t count > t table or (6.421 > 1.948). And distribution channels have a significant effect on buying interest with a coefficient of determination value of 17.8% and hypothesis testing obtained t count > t table or (4.613 > 1.948). Brand Image, Service Quality and Distribution Channels simultaneously have a significant effect on purchasing interest with the regression equation Y = 3.928X1 + 0.500X2 + -0.405X3. The coefficient of determination value is 73.1% while the remaining 26.9% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (36.732 > 2.700).